MODEL STRATEGI PEMBELAJARAN BUDI PEKERTI DENGAN PENDEKATAN KONSTRUKTIVISTIK DI SEKOLAH MENENGAH PERTAMA - Parji Parji (Universitas Negeri Malang, 2016)
The study tries to identify the difficulties and weaknesses surfacing in moral education and assess the need for and the possibility of the implementation of constructivist teaching approaches in moral education. Using a qualitative design, specifically, grounded theory, data were collected through observations, in-depth interviews, and focused group discussions from the subjects which were selected using snow-ball technique within the setting of Madiun Municipality. The data were analyzed using an interactive data analysis model. The results show that there have been serious weaknesses and difficulties in moral education brought about by internal and external factors. While the former includes those residing in the teachers (e.g., lack of innovations), school system and facilities, curriculum, and teaching-learning process, the latter encompasses such factors as limited support from the (local) government, school committee, and students' parents, and the socio-culture of the society. This study also reveals the need for the implementation of alternative instructional strategies. In this regard, the study proposes the use of constructivist paradigm in moral education.